2020
DOI: 10.1371/journal.ppat.1008335
|View full text |Cite
|
Sign up to set email alerts
|

STING promotes NLRP3 localization in ER and facilitates NLRP3 deubiquitination to activate the inflammasome upon HSV-1 infection

Abstract: One of the fundamental reactions of the innate immune responses to pathogen infection is the release of pro-inflammatory cytokines, including IL-1β, processed by the NLRP3 inflammasome. The stimulator of interferon genes (STING) has the essential roles in innate immune response against pathogen infections. Here we reveal a distinct mechanism by which STING regulates the NLRP3 inflammasome activation, IL-1β secretion, and inflammatory responses in human cell lines, mice primary cells, and mice. Interestingly, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
107
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(114 citation statements)
references
References 50 publications
(68 reference statements)
0
107
0
Order By: Relevance
“…Among others, Song et al used transfected HEK293T cells to demonstrate that NLRP3 phosphorylation mediated by JNK1 is an essential priming event for inflammasome activation [ 22 ]. Wang et al recently utilized HEK293T cells to prove that the stimulator of interferon genes (STING) binds to NLRP3 thus mediating its localization into the ER and determining its de-ubiquitination required for inflammasome activation [ 102 ]. Finally, Mao et al used HEK293T cells to demonstrate that Bruton tyrosine kinase (BTK) binds to NLRP3 to regulate its activation, therefore suggesting that BTK deficiency is associated with several inflammatory NLRP3-mediated diseases [ 103 ].…”
Section: Cell Models To Study Nlrp3 Inflammasome Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…Among others, Song et al used transfected HEK293T cells to demonstrate that NLRP3 phosphorylation mediated by JNK1 is an essential priming event for inflammasome activation [ 22 ]. Wang et al recently utilized HEK293T cells to prove that the stimulator of interferon genes (STING) binds to NLRP3 thus mediating its localization into the ER and determining its de-ubiquitination required for inflammasome activation [ 102 ]. Finally, Mao et al used HEK293T cells to demonstrate that Bruton tyrosine kinase (BTK) binds to NLRP3 to regulate its activation, therefore suggesting that BTK deficiency is associated with several inflammatory NLRP3-mediated diseases [ 103 ].…”
Section: Cell Models To Study Nlrp3 Inflammasome Biologymentioning
confidence: 99%
“…Immunofluorescence can be used to study protein expression and localization. For example, it has been reported that NLRP3 localization on mitochondria membranes under certain circumstances is required for optimal inflammasome activation [ 91 , 102 , 126 ].…”
Section: Cellular Biochemical and Biophysical Assays To Evaluatementioning
confidence: 99%
“…Herpes virus, including HHV-6 and -7 have been more frequently reported as triggers of KD [28], and, interestingly, they also activate the STING pathway. Upon HSV infection and cytosolic DNA stimulation, STING binds to NLRP3 and promotes the inflammasome activation and IL-1β release, a cytokine critically required in mouse models of KD [29].…”
Section: Introductionmentioning
confidence: 99%
“…Upon subsequent activation signals, BRCC3 removes K63‐linked ubiquitin from NLRP3, allowing inflammasome activation 37 . In addition, the stimulator of IFN genes (STING) has been shown, upon Herpes simplex virus type 1 (HSV‐1) infection and cytosolic DNA stimulation, to bind to NLRP3 and localize it to the endoplasmic reticulum, where it then removes K48‐ and K63‐linked polyubiquitination of NLRP3, facilitating inflammasome activation 38 . Additional DUBs, such as ubiquitin‐specific peptidase 7 (USP7) and USP47, have also been shown to play an essential role in regulating inflammasome activation, although they are activated primarily in response to NLRP3 activation signals like nigericin and calcium pyrophosphate dihydrate (CPPD) crystals 39 …”
Section: Ubiquitination Of Nlrp3mentioning
confidence: 99%